Evaluation of Chlorantraniliprole 150 g L-1+Fipronil 225 g L-1 SC Combination against Yellow Stem Borer and Leaf Folder in Rice - Sarkar, Prahlad; Kumar, T. Mohan; Dhanapati, Gokul Krishna; Karjee, Mrinal; Paul, Narayan Chandra; Sarkar, Maitri (International Journal of Bio-resource and Stress Management, 2026)
A field study was conducted during the kharif, 2023 and rabi, 2023–24 seasons at the Institutional Farm, Uttar Banga Krishi Viswavidyalaya, West Bengal, India to assess the efficacy of Chlorantraniliprole 150 g l-1+Fipronil 225 g l-1 SC. The experiment employed a randomized block design comprising eight treatments with three replications. The treatments included Chlorantraniliprole 150 g l-1+Fipronil 225 g l-1 SC at 50, 75, 100, and 125 g a.i. ha-1, Chlorantraniliprole 18.5% SC at 30 g a.i. ha-1, Fipronil 5% SC at 75 g a.i. ha-1, Chlorantraniliprole 9.30%+lambda-cyhalothrin 4.60% ZC at 35 g a.i. ha-1, and an untreated control. Observations focused on the % reduction in white ear heads, leaf damage, and effects on natural enemy populations per ten randomly selected hills in each plot. The findings indicated that Chlorantraniliprole 150 g l-1+Fipronil 225 g l-1 SC applied at 100 and 125 g a.i. ha-¹ achieved significant pest control (>93% reduction). Regarding grain yield, the 125 g a.i. ha-¹ dosage resulted in the highest yields (5.68 and 5.83 t ha-¹ in the first and second seasons, respectively), comparable to the 100 g a.i. ha-¹ dosage, which recorded 5.64 and 5.78 t ha-¹. However, the 100 g a.i. ha-¹ dosage exhibited the highest benefit-cost ratio and minimal impact on natural enemy populations. This study concludes that Chlorantraniliprole 150 g l-1+Fipronil 225 g l-1 SC at 100 g a.i. ha-¹ is an ecologically safe, economically viable, and effective option for pest management in the rice ecosystem.